Head injury mitigation of an adult and child pedestrian in a frontal vehicle impact using response surface methodology - Venkatason, Kausalyah; Shasthri, Sevaguru; Abdullah, Kassim Abdulrahman; Idres, Moumen; Shah, Qasim Hussain; Wong, Sha Voon (Trans Tech Publications Ltd., Switzerland, 2014)
This work aims at achieving an optimized vehicle front-end profile for improved protection for both adult and child pedestrian groups. A seven parameter simplified vehicle front end model is used in which the Central Composite Design(CCD) is utilized to generate a Plan of Experiments for the adult and child pedestrian cases each. Head Injury Criteria (HIC) results from the simulations are tabulated as the response function f(y). The Response Surface method is used to obtain mathematical models for all cases for which optimization is carried out. A close correlation is obtained between the predicted response and the response observed via simulation for the optimized models. The optimized vehicle front-end profile for the adult pedestrian group is shown to be different than that of the optimized profile for the child pedestrian. Moreover, the study shows that both optimized profiles are not mutually applicable for safety. A simple weighted biasing method is used to obtain responses that minimize the response for both adult as well as child pedestrian groups mutually within a single profile. The final optimized model is shown to achieve a safe vehicle front-end profile which equally caters for both adult and child pedestrians.